HERMENEUTIC PARADIGM IN JAVANESE PLANT METAPHOR - Arini Hidayah; I Dewa Putu Wijana; Hendrokumoro (Acceleration: Multidisciplinary Research Journal, 2025)
A metaphor is a stylistic device used to convey meaning by expressing a concept or idea through a comparison with another, distinct concept or idea. Metaphors implicitly establish a connection between two unrelated elements to provide a deeper understanding of a concept. This article specifically examines hermeneutic paradigms in Javanese plant metaphors by applying Ahimsa-Putra's paradigm theory in cultural studies. The literature review incorporates hermeneutic and metaphorical analyses from various books and journals. The study highlights that Javanese plant metaphors operate based on fundamental principles regarding their function and the way meaning is conveyed. The core principles include the recognition of comparative concepts and the use of figurative language. Metaphors help explain, illustrate, simplify, and reshape perspectives on reality. Their meaning and application vary across different contexts, cultures, and forms of communication, contributing to the clarity and expressiveness of language.